國小教師擴展學習歷程之研究 A Study of Expansive Learning Process of an Elementary School Teacher - 林盈均 Ying-Chun Lin (National Changhua University of Education, 2019)
本研究透過一位國小教師的自我敘說，陳述個人在教學場域面對各種挑戰的故事，並以活動理論作為與故事情節對話的參考架構，探究教學故事中的社會文化脈絡，呈現教師擴展學習的歷程。研究目的是以活動理論為架構，理解教師教學活動的系統及運作；從教學故事探究因擾動而產生的情境變化，並從矛盾的觀點分析其影響；探究教師面對擾動及其產生的矛盾，將如何重新詮釋教學活動。研究結果如下：（1）教學是群體活動， 應從整體脈絡來理解教學。教師實踐教學理念時，中介歷程包含工具的創造與應用、與社群成員在分工與規則中互動。活動系統是在情境脈絡中運作，中介歷程受到文化歷史因素影響，呈現社會環境的價值。（2）正向接受矛盾挑戰，有助教師擴展教學專業。教師面對擾動會感到挫折、形成矛盾張力，雖然矛盾是教師壓力來源，但在面對矛盾張力、建構解決問題策略歷程中，教師將更加瞭解問題以及環境，並擴展個人的教學專業。（3） 面對擾動與矛盾，教師能反省慎思、理解自我，並建構未來教學行動的想像。 This paper presents the self-narration of an elementary school teacher to describe stories regarding various challenges at school. Activity theory is adopted as the reference framework of story plots and dialogues so as to analyze their sociocultural context and to present the expansive learning process of the teacher. The purpose of this paper is to examine the systems and operations related to teaching activities based on the framework of activity theory. Specifically, the teaching stories are explored to observe scenario changes engendered by related disturbances, and the effects of these changes from the perspective of conflict are analyzed, thus enabling a close examination of the teacher's conflicts while experiencing these disturbances and discussing the teacher's reinterpretation of teaching activities. The conclusions of the study are as follows. (1) Teaching is a group activity and should be examined through the overall context. While actualizing their teaching ideas, teacher undergo various mediating processes, including the creation and application of teaching tools and interaction with their peers to assign tasks and define related rules. An activity system is operated under a scenario context, and mediating processes are affected by cultural and historical factors so as to demonstrate the values of the social environment. (2) Facing challenges with a positive attitude helps facilitate the development of teachers' teaching professionalism. When teachers face conflicts, they experience frustration and tension, but through the process of coping with tension and formulating problem-solving strategies, they can gain a greater understanding of related problems and the environment, helping them develop their teaching professionalism. (3) When faced with disturbances and conflicts, teachers should conduct introspection through selfunderstanding and formulate strategies for subsequent teaching activities.